Chemical composition, water vapor permeability, and mechanical properties of yuba film influenced by soymilk depth and concentration. (30th September 2017) - Zhang, Siran; Lee, Jaesang; Kim, Yookyung
Abstract: BACKGROUND: Yuba is a soy protein–lipid film formed during heating of soymilk. This study described yuba as an edible film by analyzing its chemical composition, water vapor permeability (WVP), and mechanical properties. Three yuba films were prepared by using different concentrations and depths of soymilk: HS (86 g kg −1 and 2.3 cm), LS (70 g kg −1 and 2.3 cm), and LD (70 g kg −1 and 3.0 cm). RESULTS: As yuba was successively skimmed, the protein, lipid, and SH content decreased, but carbohydrate and SS content increased. Though both the initial concentration and the depth of soymilk affect the properties of the films, the depth of soymilk influences WVP and tensile strength (TS) more. The WVP of the HS and LS changed the least (13–17 g mm kPa −1 m −2 day 1 ), while that of the LD changed the most (13–35 g mm kPa −1 m −2 day −1 ). There were no differences ( P > 0.05) in the TS between the HS and LS. LD had the greatest decrease of TS and the lowest TS among the groups. The earlier the yuba films were collected, the greater the elongation of the films was: 129% (HS), 113% (LS), and 155% (LD). CONCLUSION: The initial concentration and the depth of soymilk changed the chemical composition and structure of the yuba films. The LS yuba produced more uniform edible films with good mechanical properties. © 2017 Society of Chemical Industry